Implementation of The Integrated Islamic School Network (JSIT) Curriculum at Ihsanul Fikri Junior High School Magelang - Hidayatulloh, Faruqi; An Andari, An Andari; Ansori, Afif (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
The National Local Content curriculum, which is centered on Islamic education and consists of the National curriculum, the Islamic education curriculum, the scouting curriculum, and the skills curriculum, is integrated with the curriculum through the Integrated Islamic School Network (JSIT). The purpose of this research is to describe how the Integrated Islamic School Network (JSIT) curriculum is implemented at SMPIT Ihsanul Fikri, Magelang City, as it is realized in the school program, and to identify the factors that facilitate and hinder this implementation. This study is using a qualitative research design. The primary data sources were gathered through observation, documentation, and interviews.